Remote focal scanning and sub-volume optical projection tomography - Watson,TJ; Andrews,N; Harry,E; Bugeon,L; Dallman,MJ; French,PMW; McGinty,J (2016)
We present a platform for sub-volume optical projection tomography utilising an electrically tunable lens and tracking technology. Applied to 3D fluorescent bead phantoms and zebrafish embryos, we demonstrate an improvement in resolution and light collection efficiency with respect to conventional optical projection tomography.